2014
DOI: 10.1261/rna.048009.114
|View full text |Cite
|
Sign up to set email alerts
|

Splicing of designer exons informs a biophysical model for exon definition

Abstract: Pre-mRNA molecules in humans contain mostly short internal exons flanked by longer introns. To explain the removal of such introns, exon recognition instead of intron recognition has been proposed. We studied this exon definition using designer exons (DEs) made up of three prototype modules of our own design: an exonic splicing enhancer (ESE), an exonic splicing silencer (ESS), and a Reference Sequence (R) predicted to be neither. Each DE was examined as the central exon in a three-exon minigene. DEs made of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 70 publications
0
29
0
Order By: Relevance
“…This observation can be explained by the classical exon definition model where the shortening of the exon size below 50 nt can lead to a steric clash with the spliceosomal complexes binding to the 3 0 and 5 0 ends of exon. 42,43 Together, these result suggest that the position of the USSE element in respect to upstream 3 0 ss is dictated by the physical constraints imposed by exon definition interactions. In contrast, similar distance constraints are not apparent for canonical splicing activators (i.e.…”
Section: Discussionmentioning
confidence: 81%
“…This observation can be explained by the classical exon definition model where the shortening of the exon size below 50 nt can lead to a steric clash with the spliceosomal complexes binding to the 3 0 and 5 0 ends of exon. 42,43 Together, these result suggest that the position of the USSE element in respect to upstream 3 0 ss is dictated by the physical constraints imposed by exon definition interactions. In contrast, similar distance constraints are not apparent for canonical splicing activators (i.e.…”
Section: Discussionmentioning
confidence: 81%
“…Notably, our conclusions concerning RON splicing are robust to the precise implementation of the exon definition mechanism: in our model, we assume that U1 and U2 snRNP independently recognize splice sites, and that cross-exon and cross-intron complexes form only later during spliceosome maturation. Alternatively, exon definition may already occur at the level of initial U1 and U2 snRNP binding, because both subunits cooperate across exons during splice site recognition (9,13). In Materials and Methods, we show that both scenarios lead to the same splice isoform probability equations, implying that our fitting results also apply for strong cross-exon cooperation of U1 and U2 snRNP binding.…”
Section: High-throughput Mutagenesis Data Supports the Exon Definitiomentioning
confidence: 69%
“…To date, only a handful of mechanistic modeling studies on alternative splicing have been published. These mainly focused on the quantification of mutation effects (9,11,17), studied the impact of co-transcriptional splicing (10,18) and analyzed cell-to-cell variability of the process (19,20). Here, we approach splicing regulation from a different angle and mechanistically describe how splice site recognition by the spliceosome shapes the splicing outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…http://dx.doi.org/10.1101/199927 doi: bioRxiv preprint first posted online Oct. 8, 2017; is usually a rarer event in higher eukaryotes that contain longer introns 32 . We chose two longer intronic backbones (~300-600 bp) shown previously to not suffer from such intronic retention ( C. griseus DHFR and human SMN1 intron backbones), and found that the longer intron lengths improved both expression and assay reproducibility 33,34 . Exon inclusion metrics obtained from both of these intron contexts were highly reproducible between biological replicates (Fig.…”
Section: Main Textmentioning
confidence: 99%